2011
DOI: 10.1007/s10059-011-0073-z
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation of the Thymosin β10 Gene Is Not Associated with Its Overexpression in Non-Small Cell Lung Cancer

Abstract: Lung cancer is the leading cause of cancer-related deaths worldwide and is usually associated with a late diagnosis and a poor prognosis. Thymosin β10 (TMSB10) is a monomeric actin sequestering protein that regulates actin cytoskeleton organization. The aberrant TMSB10 expression has been implicated in the pathogenesis of human cancers. However, its role in carcinogenesis is still controversial. To better understand the role of TMSB10 in lung tumorigenesis and its regulatory mechanism, we examined the methylat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…TMSB10 is upregulated in multiple human cancers and upregulation of TMSB10 contributes to cancer cell proliferation, migration and invasion via different mechanisms, and predicts poor survival [ 13 , 15 , 31 33 ]. However, the expression of TMSB10 has also been shown to be downregualted in ovarian cancer tissues and cells and overexpression of TMSB10 diminishes tumor growth and proliferation [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMSB10 is upregulated in multiple human cancers and upregulation of TMSB10 contributes to cancer cell proliferation, migration and invasion via different mechanisms, and predicts poor survival [ 13 , 15 , 31 33 ]. However, the expression of TMSB10 has also been shown to be downregualted in ovarian cancer tissues and cells and overexpression of TMSB10 diminishes tumor growth and proliferation [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…TMSB10, a 43-amino acid residues β-thymosin, is found to be overexpressed in human lung cancer, liver cancer, breast cancer, ovarian cancer, gastric cancer, pancreatic cancer, thyroid cancer and renal cell carcinoma et al (17,20,(23)(24)(25)(26)(27). And TMSB10 mRNA is found to be overexpressed in TAMs of early lung adenocarcinoma compared with those in adjacent normal lung macrophages and peripheral blood monocytes (21).…”
Section: Discussionmentioning
confidence: 99%
“…TMSB10 mainly function as actin sequestering proteins to inhibit the formation of Factin. TMSB10 has been proven to be overexpressed in most human solid tumors, and regulate cancer cell proliferation and metastasis (16)(17)(18)(19)(20). Remarkably,Miriam Merad et al reported that TMSB10 mRNA was unregulated in TAMs of early lung adenocarcinoma compared with those in mononuclear macrophages of adjacent normal lung and peripheral blood (21).…”
Section: Introductionmentioning
confidence: 99%
“…On one hand, Tβ10 diminishes tumor growth, angiogenesis and proliferation 25 and Tβ10 over-expression has been related to the increase of apoptosis in human ovarian cancer cells 25 . On the other hand, Tβ10 has been associated to the progression of papillary thyroid carcinoma 26 and over-expression of the peptide has been observed in non-small cell lung cancer 27 and in pancreatic cancer. 28 The recent report by our group of a strong expression for Tβ10 in the human salivary glands during development, 29 induced us to better analyse the protein expression pattern for Tβ10 in the oro-gastro-intestinal tract in adult rats, in order to show if Tβ10 is expressed in the gastrointestinal tract in adulthood, and to compare the expression of this peptide with that reported in the human digestive tract and in annexed glands.…”
Section: Introductionmentioning
confidence: 99%